Genus Tisis Walker in the Malaysian Borneo, with Descriptions of Three New Species (Lepidoptera: Lecithoceridae) - Kyu, Tek Park; Joon, Joon-Seok Lee; Fatimah, Abang (Elsevier, 2005)
Twenty species of the genus Tisis Walker, including threee new species, are recognized in the Malaysian Borneo. The new species are: Tisis colubrialis sp. nov., T. penrissenica sp. nov., and T latiductalis sp. nov. Photos of adults and male or female genitalia for the new species are given. With regard to the previously known species, images of the types or voucher specimens, and figures of the male or female genitalia, that have not been well represented in previous papers, are provided. A key to species in Malaysian Borneo and a world catalogue of the genus are also provided.